Chromatic and luminance contrast sensitivity in fullterm and preterm infants - Bosworth, Rain G. (2009)
In order to investigate the contributions of visual experience vs. preprogrammed mechanisms on visual development, the current study compared contrast sensitivity in preterm vs. fullterm infants. If development is tied to time since conception, preterm infants should match the developmental trajectories of fullterm infants when plotted in postterm age. By contrast, if development is influenced by visual experience, preterm and fullterm infants should match when plotted in postnatal age. Luminance (light/dark) and chromatic (red/green) contrast sensitivities (CS) were measured in 25 preterm (born, on average, 6.6 weeks early) and 77 fullterm infants, between 1 and 6 months postterm. In the first few months, luminance CS was found to be predicted by postterm age, suggesting that preprogrammed development is sufficient to account for luminance CS. By contrast, chromatic CS exceeded that predicted by postterm age, which suggests that time since birth confers a benefit on chromatic CS. The preterms’ 6.6 weeks of additional time since birth is roughly equivalent to 3.7 weeks of development in chromatic CS. In sum, these results suggest that chromatic CS is more influenced by early postnatal visual experience than luminance CS, which may have implications for development of parvocellular and magnocellular pathways.